Visualisasi Kehilangan Ibu Berdasarkan Lagu “Fourth Of July” (Oleh Sufjan Stevens) pada Koleksi Fashion - Aninidta, Alifia Putri (BAJU: Journal of Fashion and Textile Design Unesa, 2024)
In a family, the figure of the mother generally plays a very large role. Mothers are the most influential figures in shaping children's psychology, personality and morals. The statement sparked a question. "What will happen if someone as important as 'mother' dies?" This research was made to produce visualizations based on the interpretation of song lyrics that raise the theme. To answer this question, this research was carried out by collecting secondary data related to the lyrics of a song. The song "Fourth of July" written and sung by Sufjan Stevens was raised as the theme of this research because it has lyrics that tell the moment of separation between mother and child. This research uses a creation method consisting of exploration, design and embodiment, with reference to the lyrics of the song "Fourth of July". The visualization media used is in the form of making a fashion collection. In this case, the fashion collection with the theme of the experience of a child who was abandoned by his mother as written in the lyrics of the song "Fourth of July" by Sufjan Stevens does not yet exist. This study adapts the interpretation of the song "Fourth of July" as a form of reference from the experience of losing the mother figure into a visual form in the form of a fashion collection consisting of two men's clothes and two women's clothes which each implies feelings of grief and sincerity of the mother's departure.